2008
DOI: 10.1128/jcm.00837-08
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Multiplex PCR Assay (Bruce-ladder) for Molecular Typing of All Brucella Species, Including the Vaccine Strains

Abstract: An evaluation of a multiplex PCR assay (Bruce-ladder) was performed in seven laboratories using 625 Brucella strains from different animal and geographical origins. This robust test can differentiate in a single step all of the classical Brucella species, including those found in marine mammals and the S19, RB51, and Rev.1 vaccine strains.Brucellosis is caused by a facultative intracellular bacterium of the genus Brucella, and it is one of the most frequent bacterial zoonoses in low-income countries, where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
200
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(205 citation statements)
references
References 16 publications
0
200
0
5
Order By: Relevance
“…Real-time PCR assays based on some of the genetic markers described above were later developed for Brucella species identification (Al Dahouk et al, 2007c) but these tests have the same limitations regarding B. suis and B. abortus detection. AMOS-PCR provided the basis for other multiplex PCR assays, such as the Bruce-ladder-PCR, able to successfully discriminate isolates of all six classical species and the marine mammal brucellae (Lopez-Goni et al, 2008;Mayer-Scholl et al, 2010). These tests, which are remarkably robust and require no expensive laboratory equipment, display the expected specificity at species level, except for some strains belonging to the closely related B. canis and B. suis species .…”
Section: Molecular Detection and Identificationmentioning
confidence: 99%
“…Real-time PCR assays based on some of the genetic markers described above were later developed for Brucella species identification (Al Dahouk et al, 2007c) but these tests have the same limitations regarding B. suis and B. abortus detection. AMOS-PCR provided the basis for other multiplex PCR assays, such as the Bruce-ladder-PCR, able to successfully discriminate isolates of all six classical species and the marine mammal brucellae (Lopez-Goni et al, 2008;Mayer-Scholl et al, 2010). These tests, which are remarkably robust and require no expensive laboratory equipment, display the expected specificity at species level, except for some strains belonging to the closely related B. canis and B. suis species .…”
Section: Molecular Detection and Identificationmentioning
confidence: 99%
“…Cloackaert et al ( 13 ) designed primers for amplification of omp2a and omp2b fragments and their sequences are shown in Table 1. Each PCR reaction mixture contained; 1X PCR buffer, 2 mM MgCl 2 , 1 μl template DNA (0.5 μg) , 0.15 mMdNTP, 2.5 U Taq DNA polymerase, 20 pmol of each forward and reverse primers and sterile distilled water up to 50 μl.…”
Section: Amplification Of Omp2a and Omp2b Fragmentsmentioning
confidence: 99%
“…Several molecular typing methods are introduced to find DNA polymorphism that is able to identify the Brucella species and biovars, among which detection of polymorphisms by PCR -RFLP has several advantages including the easy implementation, interpretation and use for large quantities of samples (11)(12)(13). In this method, by omp25, omp2 and omp31 loci and all Brucella species can be differentiated and their biovars identified (14).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Valve dehiscence due to ring abscesses have been reported, as was the case in our patient. 2 The clinical features of Brucella endocarditis are indistinguishable from endocarditis caused by other more common organisms. Therefore, in a patient with a strong epidemiological link, a high degree of suspicion and subsequent appropriate diagnostic evaluation is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Bruce-ladder Multiplex polymerase chain reaction confirmed that the isolate was Brucella abortus. 2 Oral doxycycline 100 mg twice daily and intravenous rifampicin 600 mg daily was commenced for a duration of 8 weeks. Gentamicin was continued for a total of 20 days.…”
Section: Introductionmentioning
confidence: 99%